KEPASTIAN HUKUM PERJANJIAN KERJA YANG DITANDATANGANI SECARA ELEKTRONIK DALAM PROSES PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL - Marie Issabella; Salmon Ginting; Roni Pandiangan (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
An employment agreement forms the legal foundation of the relationship between an employer and a worker, setting out the rights and obligations of both parties. The advancement of information technology has encouraged the use of electronic signatures in executing employment agreements, including fixed-term employment agreements, raising questions about their validity and evidentiary strength, particularly when industrial relations disputes arise. This study aims to examine the legal regulation of electronically signed employment agreements and to analyze their legal certainty as evidence in the settlement of industrial relations disputes. This research employs a normative juridical method with statutory and conceptual approaches, presented in a descriptive-analytical manner. The findings indicate that Indonesian contract law has adapted to digital technological developments as regulated under the Law on Information and Electronic Transactions (UU ITE), such that electronic employment agreements—whether signed with certified or uncertified electronic signatures—remain valid and binding provided they satisfy the requirements for a valid agreement. Nevertheless, a normative gap remains regarding whether the use of a certified electronic signature is mandatory for employment agreements. In proving industrial relations disputes, the validity of an electronic employment agreement rests not solely on the electronic document itself, but also on the entire process demonstrating the parties' electronic consent, which is recognized as valid evidence under the Law on Information and Electronic Transactions. This study recommends strengthening regulations on electronic employment agreements and establishing clearer dispute resolution mechanisms to ensure legal certainty for all parties involved.